Contact rates in wild boar populations: Implications for disease transmission. Issue 6 (1st May 2018) - Podgórski, Tomasz; Apollonio, Marco; Keuling, Oliver
ABSTRACT: Inter‐individual contacts in wildlife populations are usually highly heterogeneous. This variation translates into differential disease transmission rates between individuals, which have vital consequences for the spread, persistence, and control of infectious diseases. Wild boar ( Sus scrofa ) is an abundant game species across Europe that poses serious health threats to wildlife, livestock, and humans. However, factors shaping contact rates and structure in wild boar populations, key parameters in disease ecology, remain poorly studied. We quantified dyadic association rates, as a proxy of contacts, and individual‐based network centrality measures using telemetry data from 3 wild boar populations across Europe. Next, we examined the effect of sex, age, group membership, and space use on association rates and individual centrality. Contact rates depended strongly on the distance between individual home ranges; the most frequent associations occurred at distances of 0–1 km (mostly within groups), less frequent at 1–3 km (mostly between groups), and sporadic at >4 km. Association rates were an order of magnitude higher within social groups than between them. Between‐group association rates were only dependent on the distance between groups, with no apparent effect of animal sex or age. At the social network level, young animals (0.5–2 yr) showed greater between‐group connectivity and a more central position in the network than adults. Our results highlight substantial contact heterogeneities in wild boar populations, which should be considered in epidemiological modeling and disease control actions. First, wild boar contact rates are strongly constrained socially and spatially. Hence, management measures reducing these constraints, such as supplementary feeding and intensive hunting, may lead to increased disease transmission rates. Second, young wild boars show exceptional connectivity within the population, highlighting their high capacity for disease transmission. Therefore, targeted removal of yearlings should be considered to optimize disease control efforts. © 2018 The Wildlife Society. Abstract : Wild boar contact rates are strongly constrained socially and spatially, i.e., are much higher within social units and among animals living close together. Management measures reducing these constraints, such as supplementary feeding and intensive hunting, may lead to increased disease transmission rates. Young wild boars show exceptional connectivity within the population and targeted removal of this cohort should be considered to optimize disease control efforts.